Cutting Edge: Mycobacterium tuberculosis Induces Aerobic Glycolysis in Human Alveolar Macrophages That Is Required for Control of Intracellular Bacillary Replication. - Keane, Joseph; O'Sullivan, Mary; O'Neill, Luke; Palsson Mcdermott, Eva; Sheedy, Frederick; Gleeson, Laura (My University, 2016)
Recent advances in immunometabolism link metabolic changes in stimulated macrophages to production of IL-1β, a crucial cytokine in the innate immune response to Mycobacterium tuberculosis. To investigate this pathway in the host response to M. tuberculosis, we performed metabolic and functional studies on human alveolar macrophages, human monocyte-derived macrophages, and murine bone marrow–derived macrophages following infection with the bacillus in vitro. M. tuberculosis infection induced a shift from oxidative phosphorylation to aerobic glycolysis in macrophages. Inhibition of this shift resulted in decreased levels of proinflammatory IL-1β and decreased transcription of PTGS2, increased levels of anti-inflammatory IL-10, and increased intracellular bacillary survival. Blockade or absence of IL-1R negated the impact of aerobic glycolysis on intracellular bacillary survival, demonstrating that infection-induced glycolysis limits M. tuberculosis survival in macrophages through induction of IL-1β. Drugs that manipulate host metabolism may be exploited as adjuvants for future therapeutic and vaccination strategies.
PUBLISHED
Keywords: immunometabolism; immunometabolism; Immunology, Inflammation & Infection